2011
DOI: 10.1186/1472-6793-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic phenotyping of a cloned pig model

Abstract: BackgroundPigs are widely used as models for human physiological changes in intervention studies, because of the close resemblance between human and porcine physiology and the high degree of experimental control when using an animal model. Cloned animals have, in principle, identical genotypes and possibly also phenotypes and this offer an extra level of experimental control which could possibly make them a desirable tool for intervention studies. Therefore, in the present study, we address how phenotype and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 33 publications
5
23
0
Order By: Relevance
“…In accordance with other studies reporting on interindividual variability in pigs cloned by SCNT (Clausen et al, 2011;Hwang et al, 2009;Park et al, 2011;Whyte et al, 2011), we were not able to show significant differences between clones and controls in the interindividual variability in expression of 40 immune system-related genes in the four different tissues. The variability of serum concentrations of two of three serum proteins investigated was also similar in clones and controls, whereas the last serum protein (ORM) was significantly less variable in cloned pigs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In accordance with other studies reporting on interindividual variability in pigs cloned by SCNT (Clausen et al, 2011;Hwang et al, 2009;Park et al, 2011;Whyte et al, 2011), we were not able to show significant differences between clones and controls in the interindividual variability in expression of 40 immune system-related genes in the four different tissues. The variability of serum concentrations of two of three serum proteins investigated was also similar in clones and controls, whereas the last serum protein (ORM) was significantly less variable in cloned pigs.…”
Section: Discussionsupporting
confidence: 79%
“…Although it is normally assumed that the use of cloned animals will exhibit less interindividual phenotypic variation and allow for a reduction of the number of animals needed to obtain statistically sound data, this assumption has been found not always to be warranted. For example, the variability in blood parameters and metabolites (Archer et al, 2003;Clausen et al, 2011) as well as the gene expression of fetal growth-related genes ( Jiang et al, 2007) was found to be similar in cloned as in normal pigs. It has been proposed that some of this variation may stem from maternal mitochondrial DNA from the donor cell (St. John et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloned embryos were subsequently transferred surgically to surrogate sows (recipients) five to six days after cloning. 4 Five surrogate sows gave birth to a total of 17 female cloned pigs, during a period of three years. The non-cloned pigs (n = 19) (75% L × 25% Y) were obtained from 6 sows after standard…”
Section: Animalsmentioning
confidence: 99%
“…Cloning of pigs has been performed previously primarily by somatic cell nuclear transfer but this method often results in low numbers of cloned animals due to loss of embryos either during the gestation period or death of the piglets shortly after birth. 2,3 It has been suggested that cloning gives rise to altered metabolic characteristics, 4 skin abnormalities 5,6 and other physiological defects which may limit the use of cloned animals as experimental models. However so far there is only one study that has explored the gut microbiota in obese cloned pigs.…”
Section: Introductionmentioning
confidence: 99%